(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the theoretical foundations and practical effectiveness of technology-enhanced differentiated instruction in inclusive classrooms. The research employed pedagogical observation, questionnaires, interviews, and statistical-comparative analysis methods. The findings indicate that the use of adaptive and interactive digital platforms significantly improves students’ academic achievement, classroom engagement, and independent learning performance. In particular, technological differentiation serves as an effective mechanism for ensuring individualized instruction for students with special educational needs. The results are aligned with national and international strategies for the development of inclusive education and justify the necessity of integrating digital pedagogy into educational practice.